IMPLEMENTASI LKPD BERBASIS KURIKULUM MERDEKA UNTUK MENINGKATKAN PROFIL PELAJAR PANCASILA DIMENSI GOTONG ROYONG PADA MATA PELAJARAN PENDIDIKAN PANCASILA SISWA KELAS IV SD KHADIJAH SURABAYA - Muhdhor, Muhammad; Nafiah, Nafiah; Akhwani, Akhwani; Susanto, Rudi Umar (LPPM Institut Pendidikan Nusantara Global, 2023)
The Pancasila Student Profile is one of the efforts to improve the quality of education which prioritizes character building. LKPD can be used to develop process skills. Learning activities through LKPD provide enthusiasm for students to Think Positively and Act Positively, or a more general concept known as Learing By Doing. So that to understand the concepts learned by students better and not easily forget This research is designed using the Classroom Action Research (PTK) model, an effort to improve and / or improve learning services more professionally, Based on the results of this class action research, it can be concluded that the Student Worksheet (LKPD) in grade IV SD Khadijah Wonorejo Surabaya which is carried out in accordance with the stages above and can improve the profile of students Pancasila in students. In accordance with the formulation of the first problem, that the implementation of LKPD based on the independent curriculum to improve the profile of pancasila students in the dimension of mutual cooperation in the pancasila education subjects of grade IV students of SD Khadijah Wonorejo Surabaya there is data on the first cycle value of the first meeting of 68%, increasing in the second cycle to 86% with an increase in value of 18%.